Medicinal Chemistry and Anti-Inflammatory Activity of Nitric Oxide-Releasing NSAI Drugs - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (BENTHAM SCIENCE PUBL LTD, 2009)
Nitric Oxide, which acts as a non-specific cytotoxic mediator and a biological messenger on immunological competence, has been gaining significantly increasing importance. As an alternative to conventional NSAIDs having significant side effects, pharmacologically improved and therapeutically enhanced NO releasing non-steroidal anti-inflammatory drugs with less side effects are being planned to produce.
Keywords: Nitric oxide; NO-NSAID; anti-inflammatory; PROOF-OF-CONCEPT; INDOMETHACIN DERIVATIVES; GASTROINTESTINAL SAFETY; NITROASPIRIN NCX-4016; ACID-DERIVATIVES; CYCLOOXYGENASE-2; AGENTS; ASPIRIN; DESIGN; 5-LIPOXYGENASE